Effect of epidermal growth factor receptor expression level on survival in patients with epithelial ovarian cancer - Psyrri, A.; Kassar, M.; Yu, Z.; Bamias, A.; Weinberger, P.M.; Markakis, S.; Kowalski, D.; Camp, R.L.; Rimm, D.L.; Dimopoulos, M.A. (Clinical Cancer Research, 2005)
Background: Several lines of laboratory evidence support the epidermal growth factor receptor (EGFR) as an adverse prognostic indicator in ovarian cancers. However, different methods of immunohistochemical assessment have yielded conflicting results. Here, we sought to determine the prognostic value of EGFR in ovarian cancer using a novel method of compartmentalized in situ protein analysis. Methods: A tissue array composed of 150 advanced-stage ovarian cancers uniformly treated, with surgical debulking followed by platinum-paclitaxel combination chemotherapy, was constructed. For evaluation of EGFR protein expression, we used an immunofluorescence-based method of automated in situ quantitative measurement of protein analysis (AQUA). Results: Mean follow-up time for the entire cohort was 34.4 months. Eighty-one of 150 cases had sufficient tissue for AQUA analysis. High tumor EGFR expression was associated with poor outcome for overall survival (P = 0.0001) and disease-free survival (P = 0.0005) at 3 years. In multivariable analysis, adjusting for well-characterized prognostic variables, EGFR expression status was the most significant prognostic factor for disease-free and overall survival. Conclusion: The conflicting results in the literature regarding the prognostic value of EGFR may be due to the technical difficulties inherent in assessing EGFR with immunocytochemistry. In the present study, we show that measurement of EGFR protein levels in ovarian cancer using AQUA is feasible and can give important prognostic information. © 2005 American Association for Cancer Research.